Foreign Cry1Ab/c Delays Flowering in Insect-Resistant Transgenic Rice via Interaction With Hd3a Florigen - Fu, Jianmei; Liu, Guoqiang; Liu, Biao (Frontiers in Plant Science, 2021)
Genetic modification of rice insect resistance has been highly efficacious. However, it has also induced undesirable secondary phenotypes such as delayed flowering. The molecular mechanisms of these effects remain unclear. Here, we showed that the flowering time for the insect-resistant transgenic cry1Ab/c rice Huahui-1 (HH1) was later than that for the parental rice Minghui-63 (MH63) raised on farmland and saline-alkaline soils. In contrast, the insect-resistant transgenic cry1C* rice cultivars T1C-19 and MH63 had similar flowering times under the same conditions. We quantified mRNA transcription of the five main flowering genes in HH1, T1C-19, and MH63, florigen Hd3a protein expression in HH1 and MH63, interactions between Cry1Ab/c and the five main flowering proteins, and the influences of Cry1Ab/c protein expression on florigen Hd3a protein mediated by E3s ubiquitin ligases. Hd3a transcription in HH1 but not T1C-19 was significantly lower than that in MH63. Yeast two-hybrid, complementary bimolecular fluorescence, and co-immunoprecipitation assays disclosed that the foreign Cry1Ab/c expressed in HH1 but not the foreign Cry1C* expressed in T1C-19 interacted with florigen Hd3a. When Cry1Ab/c, Hd3a, and E3s fusion proteins were transiently co-expressed in tobacco cells, Hd3a expression was significantly lower than Cry1Ab/c and Hd3a co-expression, Thus, the Hd3a mRNA downregulation and the interaction between Cry1Ab/c and Hd3a interferes with Hd3a expression and may cooperatively delay HH1 flowering time. To the best of our knowledge, this study is the first to explain the delay in flowering time in insect-resistant transgenic rice mediated by interactions between exogenous and endogenous proteins. This information may help elucidate the molecular mechanisms of these unwanted effects and improve transgenic rice biosafety assessment.